2020
DOI: 10.3390/ijms21197011
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Starch Biosynthesis in Relation to the Building Block-Backbone Model

Abstract: Starch is a water-insoluble polymer of glucose synthesized as discrete granules inside the stroma of plastids in plant cells. Starch reserves provide a source of carbohydrate for immediate growth and development, and act as long term carbon stores in endosperms and seed tissues for growth of the next generation, making starch of huge agricultural importance. The starch granule has a highly complex hierarchical structure arising from the combined actions of a large array of enzymes as well as physicochemical se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 268 publications
(350 reference statements)
1
64
0
1
Order By: Relevance
“…Previous studies showed that the biochemical processes in mesophyll cells change with leaf age. Thus, the double-mutant dpe2/phs1 displayed an uneven distribution of starch, and the detectable starch was restricted to young leaves [ 3 , 10 ]. Most of the mesophyll cell chloroplasts in young leaves had only a single and nearly perfect spherically shaped starch granule, whereas, in mature leaves, there were no detectable starch granules, and the chloroplasts were mostly disintegrated [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that the biochemical processes in mesophyll cells change with leaf age. Thus, the double-mutant dpe2/phs1 displayed an uneven distribution of starch, and the detectable starch was restricted to young leaves [ 3 , 10 ]. Most of the mesophyll cell chloroplasts in young leaves had only a single and nearly perfect spherically shaped starch granule, whereas, in mature leaves, there were no detectable starch granules, and the chloroplasts were mostly disintegrated [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…Transitory starch is a major storer of carbon and energy, and it allows plants to overcome dark phases when photosynthesis is impossible. In recent years, huge progress has occurred toward understanding plastidial starch metabolism in the model plant Arabidopsis thaliana [ 1 , 2 , 3 ]. Generally, starch metabolism consists of two processes: synthesis and degradation.…”
Section: Introductionmentioning
confidence: 99%
“…In plants, starch appears in the form of granules in the plastids (mainly in chloroplasts of photosynthetic tissues or amyloplasts of storage organs such as tubers, endosperm, or roots) (Ball and Morell, 2003). The size, number, and morphology of these granules vary greatly depending on the species and even the organ analyzed (Tetlow and Bertoft, 2020). Starch granules are composed of two different polymers: amylose and amylopectin.…”
Section: Initiation Of the Starch Granulementioning
confidence: 99%
“…Amylopectin is the main component of starch, and has a large number of branches ordered in clusters that confer a semi‐crystalline structure to the granule. In contrast, amylose, the minor component, has a small number of branches and no known structure (Tetlow and Bertoft, 2020). The enzymatic activities involved in the formation of starch are relatively simple: ADP‐glucose pyrophosphorylase (AGPase, EC 2.7.7.27) provides ADP‐glucose, which is one substrate used by starch synthases (SSs, ADP‐Glc:α‐1,4‐glucan α‐4‐glucosyl transferases, EC 2.4.1.21) to elongate the glucan polymer chains.…”
Section: Initiation Of the Starch Granulementioning
confidence: 99%
“…During the development of grains, cereals undergo various PTMs of proteins [ 148 ]. Many of the class of enzymes involved in biosynthesis of starch are regulated and coordinated and in a range of ways from gene expression to different posttranslational mechanisms including protein phosphorylation and redox modulation [ 149 ]. Meng et al [ 147 ] also observed that the enzymes involved in starch biosynthesis and regulatory pathways, including starch branching enzymes (OsBEI and OsBEIIb), ADP-glucose pyrophosphorylases (OsAGPS2 and OsAGPL2), sucrose synthase (SUS2 and SUS3), starch debranching enzymes (OsPUL), UDP-glucose pyrophosphorylase (UGP), phosphoglycerate mutase (PGM), and starch phosphorylase (OsPHOL), in developing rice seeds undergo succinylation.…”
Section: Posttranslational Modification (Ptm)mentioning
confidence: 99%